Modelling Microstructures with OOF2. (26th May 2009) - Reid, Andrew C.E.; Lua, Rhonald C.; Garcia, R. Edwin; Coffman, Valerie R., Stephen A. Langer
OOF2 is a program designed to compute the properties and local behaviour of material microstructures, starting from a two-dimensional representation, an image, of arbitrary geometrical complexity. OOF2 uses the finite element method to resolve the local behaviour of a material, and is designed to be used by materials scientists with little or no computational background. It can solve for a wide range of physical phenomena and can be easily extended. This paper is an introduction to some of its most basic and important features.